2012
DOI: 10.1007/s00018-012-1026-1
|View full text |Cite
|
Sign up to set email alerts
|

Human skin keratinocytes, melanocytes, and fibroblasts contain distinct circadian clock machineries

Abstract: Skin acts as a barrier between the environment and internal organs and performs functions that are critical for the preservation of body homeostasis. In mammals, a complex network of circadian clocks and oscillators adapts physiology and behavior to environmental changes by generating circadian rhythms. These rhythms are induced in the central pacemaker and peripheral tissues by similar transcriptional-translational feedback loops involving clock genes. In this work, we investigated the presence of functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 38 publications
5
51
0
Order By: Relevance
“…Thus, the tail skin may possess multiple clocks of almost 24 h, but at different phases. This conclusion is in agreement with the opinion of Geyfman and Andersen (2009) and the recent study of Sandu et al (2012). The first paper claimed that it is too simplistic to define the skin as a tissue of a single circadian clock.…”
Section: Chronobiology Internationalsupporting
confidence: 91%
See 2 more Smart Citations
“…Thus, the tail skin may possess multiple clocks of almost 24 h, but at different phases. This conclusion is in agreement with the opinion of Geyfman and Andersen (2009) and the recent study of Sandu et al (2012). The first paper claimed that it is too simplistic to define the skin as a tissue of a single circadian clock.…”
Section: Chronobiology Internationalsupporting
confidence: 91%
“…Previous studies in humans and rodents demonstrated circadian rhythms in expression of several core clock genes (especially Per and Bmal1) in each of these tissues. Other experiments concluded that functional circadian clocks tick in the liver, OBs, and in most cell types in the skin (Geyfman & Andersen, 2009Granados-Fuentes et al, 2004;Guilding & Piggins, 2007;Hamada et al, 2011;Hughes et al, 2009;Kornmann et al, 2007;Liu et al, 2007;Sandu et al, 2012;Takata et al, 2002;Tanioka et al, 2009). Contradictory evidence appears to exist for the WBCs (Boivin et al, 2003;Liu et al, 2007;Teboul et al, 2005).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…33 However, human skin contains different cell types displaying a range of amplitudes in clock gene rhythms, with keratinocyte and dermal fibroblast cultures showing a more robust clock compared to melanocyte cultures. 28 To ensure that the difference in amplitude we observed between normal skin and melanoma tumors in our study is not due to a higher number of melanocytes in tumor samples, we analyzed clock gene expression in zebrafish dysplastic naevi (Fig. S2).…”
Section: Resultsmentioning
confidence: 99%
“…25,26 Skin cells have been shown to contain a robust biological clock in mammals although the function of this skin clock is generally unknown. [27][28][29][30] There is evidence for a role of the circadian clock in maintaining stem cell heterogeneity in the epidermis and the timing of DNA replication appears to be under clock-control in keratinocytes. 31,32 Analysis of clock gene expression in human skin and melanoma tumor biopsies showed down regulation in tumor samples.…”
Section: Introductionmentioning
confidence: 99%